2015
DOI: 10.3233/cbm-150484
|View full text |Cite
|
Sign up to set email alerts
|

Cyst fluid iron-related compounds as useful markers to distinguish malignant transformation from benign endometriotic cysts

Abstract: We conclude for the first time that iron-related compounds are important biomarkers that can predict malignant transformation with high sensitivity and specificity for women with endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 15 publications
5
63
1
Order By: Relevance
“…The Δl values and total Hb concentrations in 46 samples exhibited an exponential correlation (r=0.558), suggesting that the Δl value may reflect the Hb concentration. The present results were in agreement with those of Yoshimoto et al (6), who reported the cystic fluid concentration of total iron, heme iron, free iron and Hb species (6,7). Previous studies of Hb species have reported differences between OE and EAOC samples (8).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The Δl values and total Hb concentrations in 46 samples exhibited an exponential correlation (r=0.558), suggesting that the Δl value may reflect the Hb concentration. The present results were in agreement with those of Yoshimoto et al (6), who reported the cystic fluid concentration of total iron, heme iron, free iron and Hb species (6,7). Previous studies of Hb species have reported differences between OE and EAOC samples (8).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the cystic fluid Hb concentrations were reduced in patients with EAOC (6)(7)(8). The Δl values and total Hb concentrations in 46 samples exhibited an exponential correlation (r=0.558), suggesting that the Δl value may reflect the Hb concentration.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…TAC/Heme-iron ref lects the antioxidant capacity of water-soluble molecules, since the majority of iron exists as heme-iron in OE and EAOC cyst fluid samples (9).…”
Section: Introductionmentioning
confidence: 99%